EFFECT OF HEMATOCRIT LEVELS ON HbA1c VALUES IN THE ENDEMIC AREA OF HEMOGLOBINOPATHY - Sueyanyongsiri, Passorn (Journal of the ASEAN Federation of Endocrine Societies, 2023)
INTRODUCTION The utility of HbA1c may be limited due to inaccuracies in patients with hemoglobinopathy. This study aims to determine the relationship between Dtx and HbA1c levels to assess the need for control of DTx to achieve HbA1c targets in populations with hemoglobinopathy. METHODOLOGY This is a cross-sectional study that was conducted at Surin Hospital. All the data from 2016 to 2018 were analyzed for the association between variables that may affect HbA1c. RESULTS Of all the 704 patients enrolled in this study, 347 patients had negative DCIP, 204 patients had HbEA and 153 patients had HbEE. In the analysis of the relationship between Hct and HbA1c, a linear association was found. Patients with high Hct also had higher levels of HbA1c. The univariable analysis found a similar relationship between the HbEA and the control group (Y = 5.14+0.017 Dtx, R-squared = 0.1970 and Y = 4.44 + 0.020 Dtx, R-squared = 0.3288, respectively). However, the steepness of the relationship is less steep for the HbEE group at Y = 5.43 + 0.011 Dtx, R-squared = 0.1744. Furthermore, Hct was found to be weakly associated with HbA1c levels, at Y = 5.5+ 0.055 Hct and R-square = 0.0243 or 2.43%, which is highly significant at p <0.001. In addition, exploratory model multivariable analysis separating all variables to become independent found that the type of hemoglobin does not affect HbA1c. Hence, the equation derived from multivariable regression analysis is Y = 2.88 + 0.016 DTx + 0.05 Hct. CONCLUSION Suggesting that HbA1c levels are affected by Hct levels, in addition to Dtx. The eHbA1c is used to estimate the level of DTx for individual self-control by patients with altered blood concentrations.